Sosialisasi Konservasi, Sadar Wisata dan Sapta Pesona dalam Rangka Festival Pemana Bahari di Desa Pemana Kecamatan Alok Kabupaten Sikka - Desiderius Siga Meli Poa; Paulus Nong Wisang; Leonardus Winarto (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Pemana Island, located north of Flores Island, is one of the islands in the administrative area of ​​Sikka Regency which has enormous marine tourism potential. Pemana Island is included in the Maumere Bay area as a Marine Nature Tourism Park Area (TWAL), which is included in 10 large islands (Pulau Besar, Pulau Koja, Pulau Pemana, Pulau Kambing, Pulau Sukun, Pulau Parumaan, Pulau Dambila, Pulau Pangabatang, Pulau Babi and Pulau Kondo. The Pemana Bahari Festival was initiated by the Village Government by involving various parties, one of which was by inviting academics represented by the Cristo Re Polytechnic Ecotourism Study Program. The Ecotourism Study Program was invited to participate in the festival activities, especially through the socialization of educational materials on the importance of protecting the environment and nature conservation in a sustainable manner (conservation) as well as Tourism Awareness and Sapta Pesona materials. The results of this service can be used as a reference for the future in protecting the environment and nature conservation in a sustainable manner (conservation) as well as Tourism Awareness and Sapta Pesona. With this service activity, it is hoped that the Pemana village government and the local community will be able to preserve nature sustainably and apply the Sapta Pesona in Pemana Village, Alok Sub-district, Sikka Regency